The Association Between Metabolic Syndrome and Serum Leptin - Farshad Sharifi; Mojhdeh Mirarefin; Hoseyn Fakhrzade; Maryam Ghaderpanahi; Zohre Badamchizade; Bagher Larijani (University of Social Welfare & Rehabilitation Sciences, 2010)
Objectives: The relation of metabolic syndrome components, insulin resistance and leptin has been studied in elderly women. Methods & Materials: In this cross sectional study, among 225 subjects≥60 year old who were residents of Kahrizak Charity Foundation, 133 (56 men & 77 women) were selected by cluster random sampling. Fasting serum TG, Total Cholesterol, HDL, and leptin levels were measured. Results: In healthy individuals, mean age of men and women were 76.88±6.56 and 79.49±7.96 years old and in metabolic syndrome ones were 71.00±5.19 and 77.94±7.24, respectively. A total of 133 subjects were studied. Fifteen men and thirty three women were diagnosed as metabolic syndrome. There was a strong significant correlation between serum leptin level and metabolic syndrome as well as body mass index (BMI) in both sexeses (P<0.001). Among metabolic syndrome components, waist circumference showed similar correlation in both sexes. In both sexes the association between metabolic syndrome (IDF) and serum leptin was significant even after adjustment for each metabolic syndrome component with significant correlation and these components collectively (P<0.005). The association was not significant after adjustment for waist circumference. Conclusion: The current study has found that the association between metabolic syndrome and leptin in elderly might be mediated through waist circumference.